Counteracting Cisplatin-Induced Testicular Damages by Natural Polyphenol Constituent Honokiol - Tse-En Wang; Yu-Hua Lai; Kai-Chien Yang; Sung-Jan Lin; Chih-Lin Chen; Pei-Shiue Tsai (MDPI AG, 2020)
Cisplatin, despite its anti-cancer ability, exhibits severe testicular toxicities when applied systemically. Due to its wide application in cancer treatment, reduction of its damages to normal tissue is an imminent clinical need. Here we evaluated the effects of honokiol, a natural lipophilic polyphenol compound, on cisplatin-induced testicular injury. We showed in-vitro and in-vivo that nanosome-encapsulated honokiol attenuated cisplatin-induced DNA oxidative stress by suppressing intracellular reactive oxygen species production and elevating gene expressions of mitochondrial antioxidation enzymes. Nanosome honokiol also mitigated endoplasmic reticulum stress through down regulation of Bip-ATF4-CHOP signaling pathway. Additionally, this natural polyphenol compound diminished cisplatin-induced DNA breaks and cellular apoptosis. The reduced type I collagen accumulation in the testis likely attributed from inhibition of TGFβ1, αSMA and ER protein TXNDC5 protein expression. The combinatorial beneficial effects better preserve spermatogenic layers and facilitate repopulation of sperm cells. Our study renders opportunity for re-introducing cisplatin to systemic anti-cancer therapy with reduced testicular toxicity and restored fertility.